PENGEMBANGAN KEMAMPUAN SOSIAL EMOSIONAL MELALUI PERMAINAN ULAR TANGGA PADA ANAK PAUD TERPADU RESTU DI DESA PERSIAPAN TIANG BENDERA KECAMATAN HUAMUAL BELAKANG KABUPATEN SERAM BAGIAN BARAT - Wa Rasmi Husaen; Abednego; L. M. Sahetapy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social-emotional development is the process by which children learn to interact appropriately according to social norms and manage their emotions. The Snakes and Ladders game serves as effective learning media to develop children's social-emotional skills while enhancing learning motivation and social interaction. This study aims to determine whether the Snakes and Ladders game can develop social-emotional skills in children at PAUD Terpadu Restu, Persiapan Tiang Bendera Village, Huamual Belakang District, West Seram Regency. This research employed classroom action research methodology conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The study involved 12 children (5 girls and 7 boys) at PAUD Terpadu Restu. Results showed significant improvement in children's social-emotional development through the Snakes and Ladders game. In Cycle I, assessment results showed: Very Well Developed (BSB) 8.3%, Well Developed (BSH) 8.3%, Developing (MB) 50%, and Not Yet Developed (BB) 33%. In Cycle II, results improved dramatically to: BSB 75%, BSH 16%, MB 8.3%, and BB 0%. Based on these findings, it can be concluded that the Snakes and Ladders game effectively develops social-emotional skills in children at PAUD Terpadu Restu for the 2025 academic year.